2004
DOI: 10.1074/jbc.m401285200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Stimulation of Ribosomal Promoters by Binding of the +1 and +2 Nucleotides

Abstract: The rate of transcription of Escherichia coli ribosomal RNA promoters is central to adjusting the cellular growth rate to nutritional conditions. The ؉1 initiating nucleotide and ppGpp are regulatory effectors of these promoters. The data herein show that in vitro transcription is also regulated by the ؉2 nucleotide. Both the ؉1 and ؉2 nucleotides act by driving polymerase into an altered conformation rather than by increasing the lifetime of transcription complexes. The unique design of the ribosomal promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…We found that the requirement for high concentrations of initiating NTPs was specific for an initiation step prior to or including first phosphodiester bond formation. By altering the initiating (ϩ1 and ϩ2) nucleotides of several promoters we observed that, as for bacterial rRNA promoters (20,21), both the ϩ1 and ϩ2 nucleotides were very important for promoter utilization. In fact, like T7 RNAP (22) we found that the NTP used for the ϩ2 position of the transcript was needed at higher concentration than the ϩ1 NTP.…”
mentioning
confidence: 95%
“…We found that the requirement for high concentrations of initiating NTPs was specific for an initiation step prior to or including first phosphodiester bond formation. By altering the initiating (ϩ1 and ϩ2) nucleotides of several promoters we observed that, as for bacterial rRNA promoters (20,21), both the ϩ1 and ϩ2 nucleotides were very important for promoter utilization. In fact, like T7 RNAP (22) we found that the NTP used for the ϩ2 position of the transcript was needed at higher concentration than the ϩ1 NTP.…”
mentioning
confidence: 95%
“…These views are not mutually exclusive and in fact, the properties of DksA support both, as it not only destabilizes the ribosomal complexes and but also raises the K m for initiating nucleotides (Paul et al ., 2004b). This might be expected if the high K m and short lifetime were a common outcome of the effect of unusual ribosomal promoter elements on RNA polymerase structure (Lew and Gralla, 2004a). …”
Section: Molecular Mechanism Of Regulationmentioning
confidence: 99%
“…It also binds the NTPs with an usually high K m . It has been proposed that both properties are a common outcome of the unusual promoter elements imposing a distorted conformation on the bound polymerase (Lew and Gralla, 2004a). Ribosomal promoters might require NTP binding to complete the isomerization of polymerase to its functional form (Lew and Gralla, 2004b).…”
Section: Molecular Mechanism Of Regulationmentioning
confidence: 99%
See 2 more Smart Citations